A Continuously Regenerable Chiral Ammonia Borane for Asymmetric Transfer Hydrogenations. (13th August 2018) - Zhou, Qiwen; Meng, Wei; Yang, Jing; Du, Haifeng
Abstract: A novel chiral ammonia borane was designed and developed through the dehydrogenation of ammonia borane with a chiral phosphoric acid, which was highly effective for the asymmetric transfer hydrogenation of imines and β‐enamino esters to afford high levels of reactivities and enantioselectivities. Significantly, this chiral ammonia borane can be continuously regenerated during the transfer hydrogenation with the assistance of water and ammonia borane, which made it possible to obtain satisfactory results using only 0.1 mol % of the chiral phosphoric acid. Notably, the role of chiral phosphoric acid is to produce the chiral ammonia borane.